FENOMENA KOMUNIKASI PEREMPUAN SEBAGAI PENGEMUDI GO-JEK - Nurul Ardilla; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The presence of GO-JEK online transportation service application is an evidence of the rapid development of technology that has an impact or several impacts on the community, especially to facilitate transportation, fulfill customer needs, and open employment opportunities for people who want to become a driver or partner company of GO-JEK. In Pekanbaru, GO-JEK drivers are not only men but also women who certainly have more possibility of risks that might be faced compared to male drivers. This study aims to find out how the motives, the meaning of work as a GO-JEK driver, and the experience of communication of women who work as GO-JEK drivers.This study uses qualitative research method with a phenomenological approach and consists of 10 female GO-JEK drivers who were selected using the snowball technique.Data are collected through in-depth interviews, observation, and documentation. To perform data validity, the author uses extending participation and triangulation techniques. The results showed that the motives of women to be GO-JEK drivers consisted of motives which included economic demands, friend invitations, free time, and flexible work systems. As well as in order to motive, among them being successful, being able to expand friendships, hoping for God's blessing, being able to add friends and family, giving charity and benefiting the community, fulfilling needs and alleviating the family burden. Furthermore, the meaning of work for GO-JEK women drivers is a source of income (main job), part-time jobs, life experiences, reward fields, teaching the meaning of family. And the communication experience of women as GO-JEK drivers is divided into 3 momentum, namely when initiating communication when meeting customers, while serving customers, and when after serving customers. Experience pleasant communication including getting money tips, getting family and friends, getting ratings and positive reviews from customers, getting praise and appreciation, and feeling a high sense of family. The experience of communication is less pleasant, among others, getting an order with a distance too far, being insulted or considered one eye, getting a rating and negative reviews from customers, accepting cancellation of orders by passengers, and having an accident.Keyword: Phenomenon Communication, Woman, GO-JEK Drivers